Morphology and structure characterization of crystalline SnO2 1D nanostructures - Matysiak, Wiktor; Tański, Tomasz; Smok, Weronika Monika (Photonics Letters of Poland, 2020)
In recent years, many attempts have been made to improve the sensory properties of SnO2, including design of sensors based on one-dimensional nanostructures of this material, such as nanofibers, nanotubes or nanowires. One of the simpler methods of producing one-dimensional tin oxide nanomaterials is to combine the electrospinning method with a sol-gel process. The purpose of this work was to produce SnO2 nanowires using a hybrid electrospinning method combined with a heat treatment process at the temperature of 600 °C and to analyze the morphology and structure of the one-dimensional nanomaterial produced in this way. Analysis of the morphology of composite one-dimensional tin oxide nanostructures showed that smooth, homogeneous and crystalline nanowires were obtained. Full Text: PDF References N. Dharmaraj, C.H. Kim, K.W. Kim, H.Y. Kim, E.K. Suh, "Spectral studies of SnO2 nanofibres prepared by electrospinning method", Spectrochim. Acta - Part A Mol. Biomol. Spectrosc. 64, (2006) CrossRef N. Gao, H.Y. Li, W. Zhang, Y. Zhang, Y. Zeng, H. Zhixiang, ... & H. Liu, "QCM-based humidity sensor and sensing properties employing colloidal SnO2 nanowires", Sens. Actuators B Chem. 293, (2019), 129-135. CrossRef W. Ge, Y. Chang, V. Natarajan, Z. Feng, J. Zhan, X. Ma, "In2O3-SnO2 hybrid porous nanostructures delivering enhanced formaldehyde sensing performance", J.Alloys and Comp. 746, (2018) CrossRef M. Zhang, Y. Zhen, F. Sun, C. Xu, "Hydrothermally synthesized SnO2-graphene composites for H2 sensing at low operating temperature", Mater. Sci. Eng. B. 209, (2016), 37-44. CrossRef Y. Zhang, X. He, J. Li, Z. Miao, F. Huang, "Fabrication and ethanol-sensing properties of micro gas sensor based on electrospun SnO2 nanofibers", Sens. Actuators B Chem. 132, (2008), 67-73. CrossRef W.Q. Li, S.Y. Ma, J. Luo, Y.Z. Mao, L. Cheng, D.J. Gengzang, X.L. Xu, S H. Yan, "Synthesis of hollow SnO2 nanobelts and their application in acetone sensor", Mater. Lett. 132, (2014), 338-341. CrossRef E. Mudra, I. Shepa, O. Milkovic, Z. Dankova, A. Kovalcikova, A. Annusova, E. Majkova, J. Dusza, "Effect of iron doping on the properties of SnO2 nano/microfibers", Appl. Surf. Sci. 480, (2019), 876-881. CrossRef P. Mohanapriya, H. Segawa, K. Watanabe, K. Watanabe, S. Samitsu, T.S. Natarajan, N.V. Jaya, N. Ohashi, "Enhanced ethanol-gas sensing performance of Ce-doped SnO2 hollow nanofibers prepared by electrospinning", Sens. Actuators B Chem. 188, (2013), 872-878. CrossRef W.Q. Li, S.Y. Ma, Y.F. Li, X.B. Li, C.Y. Wang, X.H. Yang, L. Cheng, Y.Z. Mao, J. Luo, D.J. Gengzang, G.X. Wan, X.L. Xu, "Preparation of Pr-doped SnO2 hollow nanofibers by electrospinning method and their gas sensing properties", J.Alloys and Comp. 605, (2014), 80-88. CrossRef X.H. Xu, S.Y. Ma, X.L. Xu, T. Han, S.T. Pei, Y. Tie, P.F. Cao, W.W. Liu, B.J. Wang, R. Zhang, J.L. Zhang, "Ultra-sensitive glycol sensing performance with rapid-recovery based on heterostructured ZnO-SnO2 hollow nanotube", Mater. Lett, 273, (2020), 127967. CrossRef F. Li, X. Gao, R. Wang, T. Zhang, G. Lu, Sens. "Study on TiO2-SnO2 core-shell heterostructure nanofibers with different work function and its application in gas sensor", Actuators B Chem, 248, (2017), 812-819. CrossRef S. Bai, W. Guo, J. Sun, J. Li, Y. Tian, A. Chen, R. Luo, D. Li, "Synthesis of SnO2–CuO heterojunction using electrospinning and application in detecting of CO", Sens Actuators B Chem, 226, (2016), 96-103. CrossRef H. Du, P.J. Yao, Y. Sun, J. Wang, H. Wang, N. Yu, "Electrospinning Hetero-Nanofibers In2O3/SnO2 of Homotype Heterojunction with High Gas Sensing Activity", Sensors, 17, (2017), 1822. CrossRef X. Wang, H. Fan, P. Ren, "Electrospinning derived hollow SnO2 microtubes with highly photocatalytic property", Catal. Commun. 31, (2013), 37-41. CrossRef L. Cheng, S.Y. Ma, T.T. Wang, X.B. Li, J. Luo, W.Q. Li, Y.Z. Mao, D.J Gengzang, "Synthesis and characterization of SnO2 hollow nanofibers by electrospinning for ethanol sensing properties", Mater. Lett. 131, (2014), 23-26. CrossRef P.H. Phuoc, C.M. Hung, N.V. Toan, N.V. Duy, N.D. Hoa, N.V. Hieu, "One-step fabrication of SnO2 porous nanofiber gas sensors for sub-ppm H2S detection", Sens. Actuators A Phys. 303, (2020), 111722. CrossRef A.E. Deniz, H.A. Vural, B. Ortac, T. Uyar, "Gold nanoparticle/polymer nanofibrous composites by laser ablation and electrospinning", Matter. Lett. 65, (2011), 2941-2943. CrossRef S. Sagadevan, J. Podder, "Investigation on Structural, Surface Morphological and Dielectric Properties of Zn-doped SnO2 Nanoparticles", Mater. Res. 19, (2016), 420-425. CrossRef